1990
DOI: 10.1111/j.1755-3768.1990.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer photography in glaucomatous and normal eyes

Abstract: The technique of retinal nerve fibre photography has been developed and tested in specialized centres and glaucoma clinics. The usefullness of a modifed technique in clinical practice is the subject of this prospective study. Retinal nerve fibre photos from 41 patients with open-angle glaucoma and 40 normal patients were examined in a blind study, a total of 161 eyes. Photos from 5 eyes were of insufficient quality to allow evaluation. Nerve fibre loss was found in 36% of the normal eyes, 42% of glaucomatous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Several studies have demonstrated retinal nerve fibre loss in glaucoma. Normal eyes showed large variation in the proportion of nerve fibre loss using different photographic technics (Sommer et al 1977(Sommer et al , 1984Quigley et al 1980;Airaksinen et al 1984;Hitchings et al 1987;Pugesgaard et al 1990).…”
mentioning
confidence: 99%
“…Several studies have demonstrated retinal nerve fibre loss in glaucoma. Normal eyes showed large variation in the proportion of nerve fibre loss using different photographic technics (Sommer et al 1977(Sommer et al , 1984Quigley et al 1980;Airaksinen et al 1984;Hitchings et al 1987;Pugesgaard et al 1990).…”
mentioning
confidence: 99%